IMPROVING SPEAKING SKILL THROUGH PRESENTATION TASK AT THE FIRST YEAR STUDENTS OF PALM OIL POLYTECHNIC CITRA WIDYA EDUKASI - BEKASI - Abdulloh abdulloh (STIBA IEC JAKARTA, 2017)
This paper aims at presenting the general outline of designing oral presentations task in speaking class for college students. The presentation task is as one of varied teaching techniques in teaching speaking skill in college environment especially for students of Palm Oil Polytechnic - Citra Widya Edukasi in Bekasi, in their English I and II subjects.There are two stages in this teaching design in one session of 3 X 50 minutes. The first half of the session used for speaking practice using the module provided and the second half used for presentation task. In presentation session they gather in group for preparing the topic of presentation related with their subjects or major (Management of Logistic and Palm Oil Processing of Harvest), still in group then they work together to finish the paper and power points. Guidance of presentation is given, let them rehearse or practice at home to be moderator, presenter, speaker or other roles. In class they rehearse their presentation in group consists of five to seven students three to four times in front of different goup before the real the whole class presentation begun. This study shows that the presentation task done in group by students genereates, accelerates and empowers studens to speak english confidently. This study also has many implication that lecturers may not neglect and underestimate students’ capability. Lecturers should empower and give much oportunity to give presentation as their task. And lecturers should motivate, monitor, and facilitate them to be independent and motivated learners in English subject and other subjects in general.